2019
DOI: 10.1016/j.surg.2018.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Simplified risk prediction indices do not accurately predict 30-day death or readmission after discharge following colorectal surgery

Abstract: Background: Risk-prediction indices are one of many tools implemented to guide efforts to decreasereadmissions. Butusing simplified models to predict a complex process can prove challenging. Additionally, no risk-prediction index has been developed for patients undergoing colorectal surgery. Therefore, we evaluated the performance of a widely-utilized simplified index (LACE) and a novel index in modeling readmissions in this patient population. Methods: Using a retrospective, split-sample cohort, patients disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…[1][2][3] Readmissions have been commonly recognized as important cost drivers, 4 and several large-scale studies using national or statewide data focused on identifying potentially targetable predictors of hospital readmission. [4][5][6][7][8] However, institution-specific discrepancies due to variable care protocols, discharge criteria, or surgical settings may impede uncritical extrapolation and application of the results. Moreover, large patient cohorts are required to identify less common and potentially preventable reasons for readmission that can help focus researchers on specific outcomes of interest, such as very early readmissions.…”
Section: Principales Medidas De Resultadomentioning
confidence: 99%
“…[1][2][3] Readmissions have been commonly recognized as important cost drivers, 4 and several large-scale studies using national or statewide data focused on identifying potentially targetable predictors of hospital readmission. [4][5][6][7][8] However, institution-specific discrepancies due to variable care protocols, discharge criteria, or surgical settings may impede uncritical extrapolation and application of the results. Moreover, large patient cohorts are required to identify less common and potentially preventable reasons for readmission that can help focus researchers on specific outcomes of interest, such as very early readmissions.…”
Section: Principales Medidas De Resultadomentioning
confidence: 99%
“…Stapler et al: Interventions That Decrease Readmission e738 prediction has not been successfully modeled based on variables thought to be risk factors after colorectal surgery. 23 In contrast, another study developed a readmission risk calculator based on American College of Surgeons National Surgical Quality Improvement Program data that identified patients at high risk for readmission after colorectal surgery. Risk factors for readmission included patients with an ileostomy and those who developed postoperative SSIs.…”
Section: Discussionmentioning
confidence: 99%
“…We have done this in a previous population-level analysis of readmissions after GI surgery with the intent of improving, not restricting, generalizability of population-level research. 22 In our clinical practice, patients with LOS beyond a subjective thresholdearound 21 daysehave become a unique cohort of patients that diverge from a generalizable risk profile for post-discharge events and risk-skew data like length of stay or cost. The outlier outcomes of these patients is certainly multifactorial, but may be due to rare complications, the interaction of pre-existing comorbidities, and postoperative complications, or extensive operations (eg, multivisceral, vascular resection) with accompanying risk that is not well-captured using administrative coding.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has previously shown that, even with surgeryspecific variables and existing validated models, achieving adequate model fit when modeling readmissions using administrative data is challenging when applying models to specific patient populations. 22 Limitations of this dataset include the inability to track patients across state lines, the aforementioned limitation of the reliability of coding from administrative data, and the inexact estimation of cost from administrative charges using a conversion that varies between hospitals and years. The states selected may not be representative of states with lower population density, and we do intend to test our models using data from less populated states and data from our own institution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation